Layanan Publik Bidang Penyelenggara Haji dan Umrah Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Muhammad Kurniawan; Waizul Qarni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
Today's public services provided by government personnel are frequently found to have flaws, resulting in them failing to fulfill the community's expectations for quality. This is evidenced by the prevalence of different public criticism complaints, which can contribute to a negative image of government employees. Public service, often known as community service, is an important component that can be used to measure a government's success. The purpose of this research is to describe the challenges that the Hajj and Umrah Organizing Sector at the Regional Office of the Ministry of Religion of North Sumatra Province in Medan City, North Sumatra Province faces in providing services to the community, as well as the efforts and strategies that have been implemented. The research was descriptive qualitative in nature, with the goal of obtaining an adequate description or description of the research issue problem. According to the findings of the study, the best way to deal with the obstacles faced by the Hajj and Umrah Organizers at the Regional Office of the Ministry of Religion of North Sumatra Province is to provide services to the community that are easy/simple, short/fast, and satisfying in the implementation of licensing services, giving advice planning, and other services. It is envisaged that by putting forth these efforts, community services will be able to meet community needs while also increasing regional revenue (PAD). Keyword : Regional Office of the Ministry of Religion of North Sumatra, Public Services, Quality of Public Services